Respuesta :
Answer:
The equation of line is (y+3)=-6(x+2).
Step-by-step explanation:
It is given that the line passing through the point (-2,-3) with a slope of -6.
If a line passes through a point [tex](x_1,y_1)[/tex], then point slope form of the line is
[tex](y-y_1)=m(x-x_1)[/tex]
where, m is slope of the line.
Substitute [tex]x_1=-2,y_1=-3[/tex] and m=-6 in the above equation.
[tex](y-(-3))=-6(x-(-2))[/tex]
On simplification we get
[tex](y+3)=-6(x+2)[/tex]
Therefore the equation of line is (y+3)=-6(x+2).